Design of wave resistant structures - Loke, Edwin Jian Ping (2014)
In order to create tsunami-like waveforms, a dam gate-like mechanism was used to separate water from a large tank. The dam is then opened to simulate the tsunami. The study was motivated by prior work being done to study the wave impact on different types of structural elements. More parameters were introduced to further enhance this study. The introduction of a shield mechanism and also the usage of a new parameter, the torque, further developed the study significantly. The study made use of pressure transducers and strain gages which formed the torque meter, which are highly sensitive, to identify different loading conditions of the simulated tsunami wave. For pressure experiment, a single pressure target was used to find out the impact pressure on a structural element. An improvement was made to this experiment by adding an angled plastic target just before the element itself to simulate a shield mechanism erected in front of the structure itself. From the results of this pressure experiment, it can be clearly seen that the “shield mechanism” used greatly reduces the amount of pressure experienced by the structural element. Moreover, it also shows that the angled target is able to deflect most of the waves away from the structure. The next experiment involves using a torque meter to measure the amount of torque experienced by the stilt targets. This is a significant improvement from the previous study where only strain is being measured. The results obtained showed that the longer the stilt, the more the amount of torque is being experienced by it. This is in-line with what is being expected as when the moment arm is longer, the amount of torque experienced is greater. Moreover, the exposed surface area increases, which also increases the amount of force acting on the stilt itself. However, future work can be established to find out the threshold amount of torque a specific height of stilt can withstand. With this information available, a preliminary design of a Tsunami Resistant Structure was then created using SolidWorks which includes a Shield Mechanism, a Lifting Mechanism and a Moving Mechanism which is a Hovercraft-like moving platform. The Tsunami Resistant Structure not only is able to withstand the amount of pressure, it is able to elevate as high as it can, reducing the amount of damages to the structure and amount of casualties.